The impact of mfinance initiatives in the global south: a review of the literature - Chib, Arul (2015)
After more than two decades of research on technological interventions in the transition to information societies, the burgeoning of mobile phones in developing countries has shifted the information and communication technologies for development (ICT4D) research lens to the different domains of mDevelopment. While advances have been made in domains of mHealth, mGovernment, mBusiness and mEducation, mFinance initiatives have had impressive adoption upon implementation in certain geographic locations. Services such as M-Pesa have been widely reported in the mainstream press and form the test beds for various scholarly investigations.